PENGARUH PEMILIHAN TEMA DAN PARTNER DALAM COOPERATIVE PLAY TERHADAP PENINGKATAN PERILAKU SOSIAL PADA ANAK USIA 5-6 TAHUN DI KELURAHAN SEKARAN KECAMATAN GUNUNGPATI KOTA SEMARANG - Suroningsih, Suroningsih (Jurusan PGPAUD FIP UNNES, 2013)
Social behavior is an activites in interact with others. The purpose of this research is to know the influence of themes and partner selectedin the Cooperative Play to increase social behavior in children 5-6 years old in Sekaran, Gunungpati Semarang. The approach used is a quantitative withQuasyexperiment design, Nonequivalent control group design. The population is children 5-6 years old in Sekaran. The sample is 60 children by using cluster sampling. The technique used in the data analysis is t-test. The result of the t-test values ??treatment group were not given theme selection on social behavior is 6.426 that smaller than the value of the treatment group were given themesselection to the social behavior that 7.447. While the value of the t-test treatment group were not given the partner choice is 1,211 social behavior that smaller than the value of the treatment group were given the partner choice that 2,221 social behavior. Thestudy conclusion is there was significant influence of themes and partners selection in cooperative play against increasing of social behaviors children 5-6 years old.